2008
DOI: 10.1128/aem.00580-08
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Spores Germinate in the Chicken Gastrointestinal Tract

Abstract: A number of poultry probiotics contain bacterial spores. In this study, orally administered spores of Bacillus subtilis germinated in the gastrointestinal (GI) tracts of chicks. Furthermore, 20 h after spores were administered, vegetative cells outnumbered spores throughout the GI tract. This demonstrates that spore-based probiotics may function in this host through metabolically active mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 20 publications
4
83
0
Order By: Relevance
“…Meanwhile, tolerances to gastric (low pH) and intestinal (high bile concentration) conditions are the foundation for probiotics to survive and then colonize in the gut to produce beneficial traits [27,50]. In this study, persistence of the B. subtilis spores was assessed at high temperature, low pH, and high concentration of bile.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, tolerances to gastric (low pH) and intestinal (high bile concentration) conditions are the foundation for probiotics to survive and then colonize in the gut to produce beneficial traits [27,50]. In this study, persistence of the B. subtilis spores was assessed at high temperature, low pH, and high concentration of bile.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the allocation of enzyme activity along the small intestine showed significant differences between the proximal and distal sections associated with weaning (Collington et al, 1990). According to Cartman et al (2008), oral inoculation of B. subtilis spores (GalliPro ® ) could reduce intestinal colonisation of Escherichia coli O78:K80 in chickens.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it has been used as produced by Biochem Zusatzstoffe Handels-und Produktionsgesellschaft mbH (Lohne, Germany). Study of Cartman et al (2008) has proven that spores of B. subtilis are able to germinate in the chicken gastrointestinal tract. Also, they reported that B. subtilis spore germination occurs rapidly in the gastrointestinal tracts of chicks, with vegetative cells outnumbering spores 20 h after spore doses were administered (Cartman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus species in particular are advantageous for use as probiotics, since members of this genus are spore-formers displaying high resistance to heat, chemicals, and other stress factors (Cartman et al 2008;Chaiyawan et al 2010;Nicholson et al 2000;Setlow 2006., Bacillus spores can survive in harsh pH conditions of the gastric fluids (Cutting 2011) and reach the small intestine relatively unharmed, making them suitable for use as feed supplements. In addition, spores can be kept for a long time in desiccated form with little to no loss of viability, allowing for ease of transport (Duc et al 2004;Mazza 1994).…”
Section: Introductionmentioning
confidence: 99%